THE HISPANO-HELLENIC RELATIONSHISP DURING THE MILITARY DICTATORSHIPS OF THE GENERALS PRIMO DE RIVERA IN SPAIN AND PÁNGALOS IN GREECE (1923-1926). - Morcillo Rosillo, Matilde (Revista de Historia Social y de las Mentalidades, 2024)
This paper is an approach to the study of the  Hispano-Hellenic relationships during the  military dictatorships of the Primo de Rivera  in Spain and Pángalos in Greece, through the  Greek press, the first one, and the diplomatic  Spanish correspondence, the second one. Special importance requires the role carried  out by the Greek writer Nikos Kazantzakis as  a special correspondent of general Pángalos  to analyze the politico-economic and artistic  situation of Spain, having as backdrop the  political circumstances of both Greece and  Spain in that moment, as well as to impel the  relationships between both nations, deteriorated  after the First World War.
Keywords: Dictatorships; Primo de Rivera; Spain; Pángalos; Greece; Kazantzakis